Saliva flow rates and clinical characteristics of patients with burning mouth syndrome: A case–control study. Issue 9 (September 2021) - Werfalli, S.; Drangsholt, M.; Johnsen, J.M.; Jeffrey, S.K.; Dakhil, S.; Presland, R.B.; LeResche, L.
Abstract: Burning mouth syndrome (BMS) is a chronic pain condition that most commonly affects postmenopausal women older than 50 years of age. Xerostomia is a common complaint among BMS patients. However, previous studies showed inconsistent findings regarding saliva flow rate reduction. This study examined saliva flow rates, degree of mucosal hydration, xerostomia, and clinical characteristics in BMS patients compared with healthy controls. Unstimulated whole saliva (USWS) was collected through passive drooling; residual mucosal saliva (RMS) was collected using filter paper strips. Stimulated whole saliva (SWS) was collected while chewing on gum base. Oral exam and self-report data were collected. A total of 50 women (22 BMS cases and 28 healthy controls) aged 50 years or older were included in the analysis of this study. Mean age was 62 years for cases and 56 years for controls ( P = 0.05). Compared with controls, cases had significantly lower USWS flow rates ( P < 0.001) and had a higher prevalence of xerostomia ( P = 0.001), gastrointestinal disease ( P < 0.001), and vaginal dryness ( P = 0.01). These data show that oral and vaginal dryness are common among BMS patients. Further studies are needed to investigate potential pathophysiological mechanisms related to the quality of saliva and mucosal barrier status among these patients.